(untitled) (Damascus University Journal of arts and humanities sciences, 2026)
Documents play an important role for institutions and companies.With the entry of the artificial intelligence revolution into the field of document management, the task of processing and controlling these documents has become automated, accurate and fast, which has improved their processing, availability and increased their benefit based on the intelligent document processing. This study tries to shed light on the first project to be in the service of documents, manuscripts and archives in the Arab world, which is the Zinki project and it’s platform. The study aimed to define the concept of intelligent processing of documents and its practical application the Zinki platform detailing its features. The focus was on presenting the mechanism of its use and practical application, as well as clarifying the most important uses of artificial intelligence in the field of document management. We relied on the descriptive analytical approach as it is appropriate for the subject of the study. We analyzed the project and allocated the largest part of the analysis to the Zinki platform. The study reached a set of results, the most prominent of which was that intelligent processing of documents helps improve image quality and document segmentation. The Zinki project with its platform is considered one of the pioneering projects in the field of search systems based on artificial intelligence and the first optical search engine on letters specialized in Arabic manuscripts. It employs modern artificial intelligence methods in serving the Arabic language and manuscript heritage. Based on these results, the researcher reached a set of proposals, the most important of which was the necessity of using the Zinki platform supported by artificial intelligence to benefit from its services and also developing a guide on how to use it, as well as increasing awareness of the importance of keeping pace with technological developments in artificial intelligence and its role in document management.